2020
DOI: 10.1021/acs.jpcc.0c02443
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Modeling of Plasmonic Photothermal Heating Effects in Gold Nanoparticles and Nanoparticle Arrays

Abstract: Induced hyperthermia has been demonstrated as an effective oncological treatment due to the reduced heat tolerance of most malignant tissues; however, most techniques for heat generation within a target volume are insufficiently selective, inducing heating and unintended damage to surrounding healthy tissues. Plasmonic photothermal therapy (PPTT) utilizes light in the near-infrared (NIR) region to induce highly localized heating in gold nanoparticles, acting as exogenous chromophores, while minimizing heat gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 44 publications
2
43
0
1
Order By: Relevance
“…The photothermal effect and temperature distributions were simulated using Ansys Fluent software (Ansys Inc., Pennsylvania, USA). Here, the material properties of Au NPs, such as the absorption cross-section and thermal conductivity, can be found in the literatures 52 54 . For the simulation of the photothermal effect and temperature distributions, we assumed that (1) The system was in a steady state; (2) The incident optical power of the light source was constant; and (3) There was no convective flow.…”
Section: Methodsmentioning
confidence: 99%
“…The photothermal effect and temperature distributions were simulated using Ansys Fluent software (Ansys Inc., Pennsylvania, USA). Here, the material properties of Au NPs, such as the absorption cross-section and thermal conductivity, can be found in the literatures 52 54 . For the simulation of the photothermal effect and temperature distributions, we assumed that (1) The system was in a steady state; (2) The incident optical power of the light source was constant; and (3) There was no convective flow.…”
Section: Methodsmentioning
confidence: 99%
“…Computation of the overall optical absorption crosssection for the nanoparticle is required, considering the interparticle spacing and orientation of the nanoparticles in close proximity, for further estimation of the heat generation [4,9]. Such computation of the absorption crosssection provides assessment of photothermal conversion efficiency for clinical therapeutic applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, the optical absorption cross-sections have been evaluated for a variety of nanoparticles by considering nanosphere dimers, and GNRs homodimer or heterodimer without much emphasis on the nanoparticle configurations (location and orientations within a tissue) [6][7][8][9]17]. In one of the study, the optical properties of only spherical heterodimer for interparticle spacings of 0.2 nm and 2 nm have been reported [18].…”
Section: Introductionmentioning
confidence: 99%
“…What little work exists has explored ex vivo benchtop and early in vivo models, but demonstrated some promise that GNP photothermal heating can destroy malignant cells and inhibit tumor growth [19,23]. Gold nanorods (GNRs), among other GNP geometries, are increasingly utilized in PPTT due to their potential for high plasmonic heat generation [16,24] and optical dose tunability [25][26][27]. GNRs have been applied in numerous ex vivo and in vivo models of other varieties of cancer to explore the efficacy of PPTT [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review revealed numerous finite element (FEM) analyses describing tissue photothermal heating by NIR light [36][37][38][39]. However, only a few reported the FEM model describing the porcine pancreas tissue-NIR light (1064 nm only) interaction [24,39]. However, these models utilized porcine liver tissue thermal and optical properties instead of pancreatic tissue due to a gap in the literature on this topic [39].…”
Section: Introductionmentioning
confidence: 99%